Jovens com deficiência intelectual em um CIEJA: temas de rodas de conversa - Falcão, Caio Henrique Damasceno (2019)
The present study tried to understand what the intellectual disability students, who study at Centro Integrado de Educação de Jovens e Adultos –CIEJA, at São Paulo city. The research was schedule according to the themes, chosen by the students that composed the research group, in that way privilege the autonomy from the students and could show the principal question from the daily life from their perspective inside the inclusive education. Each theme was discussed in meetings in free talking , in that way, it was possible to have contact with the students and see the way that they have their own perception, interaction and how they are affected by the themes chosen,for example, theviolence, which is part to every single brazilian citizen, regardless their phisical and intelectual condition.